2015
DOI: 10.3390/molecules201219883
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- Specific Expression Analysis of Anthocyanin Biosynthetic Genes in White- and Red-Fleshed Grape Cultivars

Abstract: Yan73, a teinturier (dyer) grape variety in China, is one of the few Vitis vinifera cultivars with red-coloured berry flesh. To examine the tissue-specific expression of genes associated with berry colour in Yan73, we analysed the differential accumulation of anthocyanins in the skin and flesh tissues of two red-skinned grape varieties with either red (Yan73) or white flesh (Muscat Hamburg) based on HPLC-MS analysis, as well as the differential expression of 18 anthocyanin biosynthesis genes in both varieties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
(67 reference statements)
3
33
1
Order By: Relevance
“…The steps of the reaction were as follows: an initial denaturation at 95 • C for 30 s, followed by 40 cycles of amplification (denaturation at 94 • C for 10 s, followed by extension at 60 • C for 30 s). The relative expression levels of the genes were normalized to those of VvActin and calculated according to the 2 − CT method, where CT = CT target-CT VvActin (Xie et al, 2015). Three biological replicates were analyzed for each cultivar.…”
Section: Preparation Of Total Rna and Cdna And Rt-pcr Analysismentioning
confidence: 99%
“…The steps of the reaction were as follows: an initial denaturation at 95 • C for 30 s, followed by 40 cycles of amplification (denaturation at 94 • C for 10 s, followed by extension at 60 • C for 30 s). The relative expression levels of the genes were normalized to those of VvActin and calculated according to the 2 − CT method, where CT = CT target-CT VvActin (Xie et al, 2015). Three biological replicates were analyzed for each cultivar.…”
Section: Preparation Of Total Rna and Cdna And Rt-pcr Analysismentioning
confidence: 99%
“…The white color of the grape varieties is caused by mutations that occur in the VvmybA1 gene which controls the formation of anthocyanins. All white grapes have a common origin (Walker et al, 2007;Fournier-Level et al, 2009;Xie et al, 2015). Xie et al (2015) stated that the red color of Alicanthe Bouschet began to appear in the flesh before the skin.…”
Section: Inheritance Of Anthocyaninsmentioning
confidence: 99%
“…Previous studies of other species [ 28 , 29 , 30 ] have shown that the expression of most of the anthocyanin pathway genes is higher in dark fruits compared to white ones. In spite of the variable expression of genes involved in the flavonoid pathway in different species and tissues, a certain correlation with anthocyanin accumulation has been found [ 30 ].…”
Section: Introductionmentioning
confidence: 99%